Evaluation of Osteoporosis Among Epileptic Patients on Monotherapy - Mufeed Akram Taha; Neven Nihal Hana Istifo (College of Pharmacy University of Baghdad, 2024)
Epilepsy is a common chronic neurological disorder that affects almost 50 million people worldwide. Most patients require long-term, and sometimes lifelong therapy with antiseizure medications (ASMs), our case control study evaluates the long-term effect of carbamazepine (CBZ) and valproate (VPA) on bone mineral density and bone health biochemical markers. 50 patients with newly diagnosed epilepsy who had no history of antiseizure medications (ASMs) intake prior were divided into 2 groups. In the first group, 25 patients started carbamazepine (CBZ) monotherapy, while the second group included 25 patients who started receiving valproate (VPA) monotherapy. Another 25 healthy individuals were considered as a control group. The primary outcome of our study is to evaluate the percentage of osteoporosis compared to the duration of ASM therapy measured by the T score at two different sites in the body at baseline, after 3 and 6 months of therapy, while measurements of bone biomarker variables are considered secondary outcomes. We found that CBZ and VPA significantly decreased the level of vitamin D3, Ca, P, the L3-L5, and right femoral neck T score with prolonged treatment duration, while the level of ALP increased with increasing duration of treatment in patients treated with CBZ but not in the VPA group. Furthermore, CBZ significantly decreased bone health biomarkers and T score before VPA and the control group, as well as there were no significant differences between the two sexes who received CBZ or VPA therapy on bone biomarkers. In conclusion, valproate will not affect bone biomarkers earlier, but with a longer duration of therapy, they may have the same effect as carbamazepine which requires the prescription of supportive vitamin D and Ca along with ASMs.